Principal Entrepreneurship in Building Effective Learning Resources - Qomariyah, Titik Nur; Soenaryo, Siti Fatimah; Syahri, M. (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to analyze the entrepreneurial competency of the Principal of Muhammadiyah 1 Jombang Elementary School in creating innovative, sustainable, and relevant learning resources to meet the needs of the times. Using a qualitative phenomenological approach, Research data was collected through triangulation techniques, namely unstructured in-depth interviews, participant observation, and documentation. Research data was collected through triangulation techniques, namely unstructured in-depth interviews, participant observation, and documentation, this study explores the subjective experiences of the principal as an agent of change through in-depth interviews, participant observation, and documentation, strengthened by triangulation of sources and techniques. The data analysis technique refers to the Miles and Huberman model, which includes three sequential stages: (1) data reduction, namely sorting, focusing, and simplifying raw data into meaningful units based on research themes; (2) data presentation, in the form of compiling findings in the form of thematic narratives and analytical tables to clarify patterns and relationships between categories; and (3) drawing conclusions and verification, where researchers identify core meanings, consistent patterns, and phenomenological interpretations that emerge from verified data. The results show that the principal understands entrepreneurship not only as an economic activity, but as a transformative leadership strategy to develop a dynamic learning ecosystem. Innovations such as Batik, Al-Islam Textbooks, Madrasah Cooperatives, Used Cooking Oil Programs, and IPMKids are concrete manifestations of utilizing local resources into contextual learning resources. Despite facing limited facilities and funds, the principal successfully optimized internal potential through collaboration, an innovative culture, and the integration of entrepreneurship into the Madrasah Operational Curriculum. The impact is seen in increased motivation, independence, and understanding of student academic concepts, which are reflected in the Mathematics and Science learning process, as well as the transformation of the teacher's role into an active learning facilitator. This research confirms that educational quality does not depend on the completeness of infrastructure, but rather on the entrepreneurial spirit of visionary, adaptive, and student-centered leadership. This research is expected to inspire other madrasas in developing holistic, inclusive, and sustainable education.